Effect of a program of functional reeducation in the sênior people's flexibility - Caromano, Fátima Aparecida; Mendes, Felipe Augusto dos Santos (Revista de Terapia Ocupacional da Universidade de São Paulo, 2000)
The aging produces alterations in almost ali the organic systems, mainly in the muscular and skeletal system. One of the most frequent alterations is the decrease of the muscular elasticity and the increase of the rigidity of several articulations that cart decrease of movement affecting the mobility. This study had for objective to evaluate the effect of a program of functional reeducation in the sênior people's flexibility, through the photographic method. We met significant improves in the flexibility and in the leveis of the superior members during the test third modified finger-ground, after the application of the program.